2023
DOI: 10.21203/rs.3.rs-2518888/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient photo-adsorptive eradication of endocrine disrupting pesticides by chitosan co- decorated metal oxide bio-nanocomposite

Abstract: Extensive consumption, toxicity, and bioaccumulation of malathion (MLT) and lindane (γ-HCH) pesticides collectively attract the world’s attention. Herein, the nanocomposite of chitosan wrapped NiO@ZnO was synthesized by a green methodology using Azadirachta indica leaves extract. Structural and morphological analysis of chitosan-NiO@ZnO showed hollow sphere-flake shaped image adsorbed on a solid chitosan surface with a large surface area of 73 m2g-1. A decrease in values of lattice strain, dislocation density … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Through literature surveys, it was observed that Ag doped nanocomposites such as Ag@ZnONSt, 19 Ag/LaTiO 3, 20 CuO/TiO 2 /PANI, 21 Ag‐CuS, 22 Ag/ZnO, 23 and graphene/Ag‐doped TiO 2 24 are synthesized for the removal of selected pesticides shown Table 2. Because of environmental concerns and the implication of green chemistry, there is the trend for the synthesis of doped nanoparticles using plant feedstock (plants, roots, flowers, leaves) which contain several types of phytochemicals such as polyphenols, cellulose, saponins, sugars, flavonoids, and amino acids 25–31 . Therefore, it was envisioned to synthesize silver‐doped metal hexacyanoferrates (Ag@MHCFs) via the green route.…”
Section: Introductionmentioning
confidence: 99%
“…Through literature surveys, it was observed that Ag doped nanocomposites such as Ag@ZnONSt, 19 Ag/LaTiO 3, 20 CuO/TiO 2 /PANI, 21 Ag‐CuS, 22 Ag/ZnO, 23 and graphene/Ag‐doped TiO 2 24 are synthesized for the removal of selected pesticides shown Table 2. Because of environmental concerns and the implication of green chemistry, there is the trend for the synthesis of doped nanoparticles using plant feedstock (plants, roots, flowers, leaves) which contain several types of phytochemicals such as polyphenols, cellulose, saponins, sugars, flavonoids, and amino acids 25–31 . Therefore, it was envisioned to synthesize silver‐doped metal hexacyanoferrates (Ag@MHCFs) via the green route.…”
Section: Introductionmentioning
confidence: 99%